Coping and its relationship to post-traumatic growth, emotion, and resilience among adolescents and young adults impacted by parental cancer. Issue 1 (2nd January 2020) - Morris, Julia N.; Turnbull, Deborah; Martini, Angelita; Preen, David; Zajac, Ian
Abstract: Purpose: This study investigated how coping impacts offspring's adaption to parental cancer in terms of post-traumatic growth, resilience, and emotion; and how coping differs between offspring. Methods: Participants (18–34 years; n = 244) completed an online survey. Data were analyzed using generalized linear modeling and multinomial regression. Findings: Higher levels of adaptive coping was associated with higher post-traumatic growth, resiliency, and positive affect; whereas maladaptive coping was associated with lower resiliency and higher negative affect. Females and offspring who did not access support for their parent's cancer reported higher adaptive coping. Offspring bereaved by parental cancer reported higher levels of maladaptive coping. Offspring whose parents' cancer was of shorter duration and those who lived with their ill parent had lower adaptive and maladaptive coping. Conclusions/Implications: Adaptive coping appeared beneficial to offspring. Supportive interventions may benefit from focusing on increasing adaptive coping, particularly among bereaved offspring.